Fungal Genetics Stock Center Catalogue of Strains, 9th edition - Kevin McCluskey; John A. Kinsey (Fungal Genetics Reports, 2002)
Catalogue of Strains, 9th edition, 2002, supplement to Fungal Genetics Newsletter No. 49. This catalogue contains lists of materials held by the Fungal Genetics Stock Center.